Influence of sputtering temperature of TiO2 deposited onto reduced graphene oxide nanosheet as efficient photoanodes in dye-sensitized solar cells - Low F.W.; Hock G.C.; Kashif M.; Samsudin N.A.; Chau C.F.; Utami A.R.I.; Islam M.A.; Heah C.Y.; Liew Y.M.; Lai C.W.; Amin N.; Tiong S.K. (MDPI AG, 2023)
coloring agent; graphene oxide; graphite; nanoparticle; titanium; titanium dioxide; chemical structure; chemistry; electrode; oxidation reduction reaction; particle size; photochemistry; power supply; solar energy; surface property; temperature; Coloring Agents; Electric Power Supplies; Electrodes; Graphite; Molecular Structure; Nanoparticles; Oxidation-Reduction; Particle Size; Photochemical Processes; Solar Energy; Surface Properties; Temperature; Titanium